Evaluation of a mobility/QoS-aware architecture for mobile internet - Lopes, Nuno Vasco (2012)
This paper addresses the issue of mobility and QoS management principles as well as the mobility and QoS management integration in the sense of build a QoS-aware architecture for mobile Internet. After covering the mobility and QoS management principles and integration, this paper also proposes a new QoS-aware architecture for mobile Internet. This new architecture takes into account the specific characteristics of mobile networks in order to design an integrated Mobility/QoS-aware management architecture suitable for realtime applications requirements. The solution avoids network congestion as well as the starvation of less priority DiffServ classes while increasing resource utilization for priority classes while maintaining the QoS offer to MN's applications by making each DiffServ class unchangeable with MNs mobility. The proposed mobility management model is simple, easy to implement, and takes into consideration mobile internet requirements. It proved to be capable of providing Internet applications running in mobile devices with acceptable levels of quality of service. The simulation results indicate that the suggested architecture is able to provide acceptable QoS levels to real-time applications that are running in mobiles devices. © 2012 CCIS.